The Mozart Expositional Punctuation Corpus: A Dataset of Interthematic Cadences in Mozart's Sonata-Allegro Exposition - Raz, Omer; Chawin, Dror; Rom, Uri B. (Empirical Musicology Review, 2021)
This report documents a dataset consisting of expert annotations (symbolic data) of interthematic (higher-level) cadences in the exposition sections of all of Mozart's instrumental sonata-allegro movements.